Surface modification of Ti dental implants by Nd: YVO4 laser irradiation - Braga, Francisco J. C.; Marques, Rodrigo Fernando Costa [UNESP]; Filho, Edson de A.; Guastaldi, Antonio Carlos [UNESP] (Elsevier B.V., 2007)
Surface modifications have been applied in endosteal bone devices in order to improve the osseointegration through direct contact between neoformed bone and the implant without an intervening soft tissue layer. Surface characteristics of titanium implants have been modified by addictive methods, such as metallic titanium, titanium oxide and hydroxyapatite powder plasma spray, as well as by subtractive methods, such as acid etching, acid etching associated with sandblasting by either AlO2 or TiO2, and recently by laser ablation. Surface modification for dental and medical implants can be obtained by using laser irradiation technique where its parameters like repetition rate, pulse energy, scanning speed and fluency must be taken into accounting to the appropriate surface topography. Surfaces of commercially pure Ti (cpTi) were modified by laser Nd:YVO4 in nine different parameters configurations, all under normal atmosphere. The samples were characterized by SEM and XRD refined by Rietveld method. The crystalline phases alpha Ti, beta Ti, Ti6O, Ti3O and TiO were formed by the melting and fast cooling processes during irradiation. The resulting phases on the irradiated surface were correlated with the laser beam parameters: the aim of the present work was to control titanium oxides formations in order to improve implants osseointegration by using a laser irradiation technique which is of great importance to biomaterial devices due to being a clean and reproducible process. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: surface modification; titanium; laser ablation; dental implant; biomaterial